PENINGKATAN HASIL BELAJAR MELALUI AN ANALYSIS GUIDED DISCUSSION METHOD MATERI JURNAL UMUM DI KELAS 12 IPS SMAN 1 PEKALONGAN - YL. Bambang Purwanto (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The fundamental problem of IIS 12th grade students in understanding accounting lessons is that they start from not being well understood how to record transactions in a journal. Difficulty understanding the accounting material for these students can be seen from the initial test conducted on July 24, 2018 in 12th grade IIS turned out in completing the journal of the number of students 32 people there were 26 (81.25%) students had not reached the KKM and who had only reached 8 (18.75%) students with minimum completeness criteria (KKM) of 70.  In the initial test before using an analysis guided discussion,  student learning outcomes obtained an average of 32.14. Whereas in the first cycle test has been applied an analysis guided discussion obt79ained an average of 54.43. In the second cycle the results obtained were an increase in the average score of a fairly high class that is to be 75.94 Although in the second cycle has reached a fairly high average of 75.94, but the researchers still proceed to cycle III because the percentage of completeness is only amounting to 62.5. The results of the third cycle average value of 93.43 with a completeness level of 87.5%.    Keywords: Learning Outcomes, An Analysis Guided, Discussion Method